Propriedade intelectual na administração pública estadual : proposta de modelo de gestão para Mato Grosso - Gagini, Débora Lopes (2023)
Public innovations are not restricted to the environment of Innovation Laboratories and Scientific, Technological and Innovation Institutions (ICTS), they can occur throughout the Public Administration (PA). Therefore, the management of these innovations in public organizations becomes a more complex process that demands management strategies, in a clear and objective way, so that all those involved can previously know the guidelines and procedures for the protection of intellectual creations developed within the scope from PA. Starting from the systematic review of the literature, it was found that there are no papers that discuss the implementation of specific Intellectual Property (IP) management actions in the public sector, in addition to ICTS. Thus, this research aimed to develop an IP management model for the Government of the State of Mato Grosso, in addition to contributing to the construction of a theoreticalconceptual IP management model that meets the managerial needs of the public sector in general. As these are technological and innovative products, the methodology of the Lean Startup cycle (Build-Measure-Learn) was applied for internal and external validation of the business model. From data collection and benchmarking analysis, it was concluded that IP urgently deserves to enter the agenda of innovation-promoting environments in PA Direct.